Evaluasi Cambridge International Primary Program Siswa SD Al-Azhar pada Mata Pelajaran ’English Language’ - Ria Herwandar; Denny Azhari Safryono (Universitas Al Azhar Indonesia, 2014)
Abstrak – Analisis materi ujian bahasa Inggris Cambridge Primary Checkpoint merupakan bagian dari penelitian Evaluasi Cambridge International Primary Program siswa SD Al-Azhar pada mata pelajaran “English Language. Peneliti ingin membuktikan bahwa teori pemerolehan bahasa ke dua pada anak usia dini dapat dibuktikan melalui hasil capaian ujian yang dikelola oleh Cambridge. Terbukti bahwa anak (usia 12-130) mampu menguasai bahasa ke dua dengan baik apabila dilaksanakan dengan benar. Abstract – The analysis of English Examination of Cambridge Primary Checkpoint has been a part of the research with the title “Evaluation of Cambridge International Primary Program of elementary students of Al-Azhar on ‘English language’”. The researcher wishes to identify that the theory of second language aquisation on children has been proved adequately through the analyses of examination results which has been conducted in Al-Azhar primary school. It is identified that children (age 12-13) are capable of mstering other language when it is given in the proper manner. Keywords – Cambridge Primary Checkpoint, reading, writing ,usage and evaluation